ANALISIS KEBIJAKAN PEMERINTAH REPUBLIK INDONESIA DALAM MENGHADAPI PANDEMI COVID-19 - Kurhayadi (GoAcademica Research dan Publishing, 2021)
The spread of Covid-19 in Indonesia is taking place very quickly and continues to grow rapidly. This causes the need for a policy to be able to overcome the problem of the Covid-19 pandemic. The purpose of carrying out this research is to be able to analyze how the policies made by the government in responding to the emergence of the Covid-19 pandemic. This research will be carried out using a qualitative approach. The data used in this study comes from the results of previous studies or studies that still have a similar discussion with this article. The results of this study found that in early March 2020, Indonesian state policies were still quite slow in responding to the emergence of the first Covid-19 virus. Currently, the Indonesian government has created several policies such as Large-Scale Social Restrictions or physical distancing. However, this policy is very dependent on the obedience of the community. The Indonesian people themselves can be the key to the success of government policies, or even become the biggest obstacle for the government itself.